ANALYSIS OF MATHEMATIC HIGH ORDER THINKING SKILLS (HOTS) PROBLEMS BASED ON COGNITIVE LEVEL INDICATORS ON BLOOM TAXONOMY - LIA AMALIA (Jurnal Riset Pendidikan Matematika Jakarta, 2021)
Abstract. This study aims to analyse the questions of high order thinking skills in the Statistics chapter in 2013 curriculum Mathematics textbook which are measured based on indicators of cognitive levels in Bloom's taxonomy. The object of this study is the questions in the Statistics chapter in the Mathematics textbook which is 3 questions. The question analysis technique is based on problem solving with details of competency standards, question indicators, HOTS indicators, Questions and Answer Keys. Keywords: High Order Thinking Skills, Statistics, Bloom's Taxonomy